The First Seven Days Matter: Knowledge and Attitudes of Postpartum Mothers Toward Newborn Care - A Cross-Sectional Study in Buleleng Regency - Ketut Espana Giri; Sumiati Sumiati; Yuni Kurniawati (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: The first 0–7 days of life represent the most critical period for neonatal survival, with a high risk of morbidity and mortality. Although maternal knowledge and attitudes are considered key determinants of newborn care, evidence regarding their influence on actual practices remains inconsistent. Method: A cross-sectional analytic study was conducted among 128 postpartum mothers selected using purposive sampling. Data were collected using validated questionnaires measuring knowledge, attitudes, and newborn care practices. Data analysis was performed using Chi-square and Fisher-Freeman-Halton Exact tests with a significance level of 0.05. Result: Most respondents had good knowledge (66.4%), very positive attitudes (79.7%), and good newborn care practices (94.5%). A significant association was found between maternal knowledge and newborn care practices (p < 0.001), indicating that higher knowledge is associated with better practices. However, maternal attitudes were not significantly associated with practices (p = 0.136), despite the predominance of positive attitudes. Conclusion: Maternal knowledge plays a critical role in shaping newborn care practices, whereas positive attitudes alone are insufficient to ensure appropriate behavior. Conclusion: highlight a gap between attitude and practice, emphasizing the importance of contextual and enabling factors. Strengthening maternal and child health programs should focus on skill-based education, structured postnatal counseling, and family support to ensure effective translation of knowledge into practice